Detection of peripheral and central sensitisation at acupoints in patients with unilateral shoulder pain in Beijing: a cross-sectional matched case–control study. Issue 6 (15th June 2017) - Yan, Chao-Qun; Zhang, Shuai; Li, Qian-Qian; Zhang, Li-Wen; Wang, Xue-Rui; Fu, Qing-Nan; Shi, Guang-Xia; Liu, Cun-Zhi
Abstract : Objective: To investigate the pattern of experimental pain responses at acupoints in patients with unilateral shoulder pain. Design: A cross-sectional matched study. Setting: Acupuncture and Moxibustion Department, Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University. Participants: Volunteer samples of 60 participants (30 patients with unilateral shoulder pain, 30 healthy controls). Interventions: Not applicable. Main outcome measures: Pressure pain thresholds (PPTs) were measured at four acupoints—namely, Tianzong (SI 11), Jianliao (SJ 14), Jianyu (LI 15) and Jianzhen (SI 9), on the painful/non-painful side in patients with unilateral shoulder pain or healthy controls, respectively. The correlations between the Peripheral Sensitisation Index (PSI) and Central Sensitisation Index (CSI) were compared. Results: Analysis showed significantly lower PPT values at acupoints on the painful side compared with the non-painful side in patients with shoulder pain (p<0.025). Meanwhile, PPTs on the non-painful side of these patients were lower than those on the ipsilateral side of healthy controls (p<0.025). No significant differences in PPT values were found between the non-acupoint of the painful/non-painful side in patients with shoulder pain and the ipsilateral side of healthy controls (p>0.05). Additionally, it was observed that the pressure pain assessment acupoints have a strong association with PSI and CSI; three acupoints, in particular, SJ 14, LI 15 and SI 9, showed a correlation with PSI and CSI. Conclusion: The results suggest the presence of peripheral and central sensitisation at acupoints in participants with unilateral shoulder pain. There exists an obvious relationship among the three acupoints SJ 14, LI 15 and SI 9, which are usually chosen to treat shoulder pain. The results provide evidence for the selection of acupoints to treat shoulder pain by acupuncture.